Milking management clinics - James R. Dunham; Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1988)
Thirty Milking Management Clinics have been conducted at various on-farm locations. The clinics have demonstrated that good milking techniques can result in an additional 1891 lb milk yield/cow in a 10-mo lactation and an increased milk flow rate of 0.9 lb/min. Additional demonstrations include: I) teat dipping techniques, 2) proper sanitation programs, 3) antibiotic sensitivity culturing, 4) residue avoidance programs, 5) dry cow treatment techniques, and 6) milking equipment evaluation.; Dairy Day, 1988, Kansas State University, Manhattan, KS, 1988;
Keywords: Kansas Agricultural Experiment Station contribution; no. 89-107-S; Dairy; Milking management; Milk secretion; Milk let-down